Benign paroxysmal torticollis in infancy – diagnostic error possibility - Zlatanović Dragan; Dimitrijević Lidija; Stanković Anita; Balov Biljana (Vojnosanitetski Pregled)
Background/Aim. Benign paroxysmal torticollis (BPT) is a rare paroxysmal dyskinesia characterized by attacks of head tilt alone or tilt accompanied by vomiting and ataxia, which may last hours to days. It is claimed that BPT disappears completely in childhood, but that it can evolve into other conditions, such as benign paroxysmal vertigo, cyclical vomiting syndrome, abdominal migraine, hemiplegic migraine, motion sickness and/or migraine with aura. The aim of this manuscript was to renew focus on benign paroxysmal torticollis because the disorder is almost always under-recognized by pediatric practitioners, who often order extensive and unrewarding testing and physiotherapy treatment. Methods. Twelve BPT cases observed during a 5-year period (2009–2014) at the Clinical Centre Niš, Niš, Serbia were reviewed. Data were collected on the features of torticollis, the age of onset, the duration of episodes, associated symptoms, the frequency of episodes, the persistence of symptoms over time, the age when the disorder finally disappeared, sequelae appearing after the 5th birthday, and family history of BPT, migraine or kinetosis. All the children were followed for periods ranging from 48 to 72 months. Results. The series included 6 females and 6 males. The age at onset of BPT was less than 8 months in 84% of the cases. Episodes of torticollis occurred suddenly on waking in all the cases without any trigger factors. The duration of torticollis ranged from a few hours to a few weeks. In 58% of cases, the condition persisted for more than one week. The frequency of the episodes ranged from once every 3 days to once every 25 days. The episodes were more frequent and lasted longer in the early months and tended to cease as the child became older. The age when episodes ended ranged from 11 months to 62 months. In 11 (91.66%) cases, the disorder disappeared before the patient's 5th birthday. No patient had a family history of BPT. In 6 cases, family members had kinetosis. In 5 cases, family members were positive for both migraine and kinetosis. All the children had normal motor development and normal speech and language development. After the disappearance of BPT, two children developed other forms of periodic syndromes: one boy had migraine with aura, and one girl experienced cyclic vomiting. Conclusion. BPT is probably an age-sensitive and migraine-related disorder that is benign in nature. The disorder is often misinterpreted, and children may pointlessly undergo numerous tests. Therefore, it is very important to recognize and observe this condition in order to avoid extensive, unnecessary and unpleasant procedures on the child.